1996
DOI: 10.1007/bf02510039
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of 5S and 18S–28S rDNA loci in a tetraploid cotton (Gossypium hirsutum L.) and its putative diploid ancestors

Abstract: The most widely cultivated species of cotton, Gossypium hirsutum, is a disomic tetraploid (2n=4x=52). It has been proposed previously that extant A- and D-genome species are most closely related to the diploid progenitors of the tetraploid. We used fluorescent in situ hybridization (FISH) to determine the distribution of 5S and 18S-28S rDNA loci in the A-genome species G. herbaceum and G. arboreum, the D-genome species G. raimondii and G. thurberi, and the AD tetraploid G. hirsutum. High signal-to-noise, singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(69 citation statements)
references
References 18 publications
6
62
0
1
Order By: Relevance
“…Results of the FISH analysis at mitosis showed that G. hirsutum (A t A t D t D t ) carried six 45S loci with two loci on A t genome (Figure 5, A and B), in accordance with previous reports (Hanson et al 1996; Gan et al 2013). However, six 45S loci were also observed on the A genome of G. herbaceum (A 1 A 1 ) (Figure 5C).…”
Section: Resultssupporting
confidence: 90%
“…Results of the FISH analysis at mitosis showed that G. hirsutum (A t A t D t D t ) carried six 45S loci with two loci on A t genome (Figure 5, A and B), in accordance with previous reports (Hanson et al 1996; Gan et al 2013). However, six 45S loci were also observed on the A genome of G. herbaceum (A 1 A 1 ) (Figure 5C).…”
Section: Resultssupporting
confidence: 90%
“…Thus, physical association of rDNA clusters between both homologous and nonhomologous sites is possible, supported by the fact that rDNA-bearing chromosomes appear to be non-randomly associated with each other at mitotic metaphase [36]. It is widely accepted that association of genes with highly repetitive sequences would increase the opportunity for unequal exchanges.…”
Section: Discussionmentioning
confidence: 99%
“…Size polymorphism of the hybridization signals, among and within homologous sites could be explained by such events. On the other hand, somatic exchanges taking place between different sites could make homogenization and changes in rDNA copy number occur especially quickly [36]. Therefore, it is reasonable to suggest that the rDNA repeats in strawberry are in a highly dynamic state because of their terminal positions and potentially high degree of association between sites.…”
Section: Discussionmentioning
confidence: 99%
“…FISH mapping of ribosomal DNAs directly on the chromosomes provides a useful approach for identification of chromosome and studies of chromosome organization and evolution. FISH has been applied to conduct the physical mapping of chromosomes in important economic and medicinal plants, and the organization and differentiation of rDNAs in closely related species has provided important information for analysis of chromosome evolution and species formation (Abbo et al 1994;Hanson et al 1996;Adachi et al 1997;Chen et al 1999;Taketa et al 1999;Han et al 2008;Martina et al 2010;Zhao et al 2011). To extend our knowledge of chromosome organization and evolutionary changes of wild species of Cucumis, we conducted FISH experiments with 45S and 5S rDNA probes on metaphase spreads of 20 Cucumis accessions to investigate their site numbers and physical positions.…”
Section: Introductionmentioning
confidence: 99%